Usefulness of early lung ultrasound in acute mild-moderate acute bronchiolitis. A pilot study - Elia Zoido Garrote; Cristina García Aparicio; Constanza Camila Torrez Villarroel; Antonio Pedro Vega García; Manoel Muñiz Fontán; Ignacio Oulego Erroz (Elsevier, 2019)
Objective: To determine the correlation between the findings seen in early lung ultrasound with the clinical severity scales, and its association with the subsequent progression of the mild-moderate acute bronchiolitis (AB). Patients and methods: An observational prospective study conducted on infants with mild-moderate AB, using lung ultrasound in the first 24 h of hospital care. The lung involvement was graded (range 0-50 points) based on an ultrasound score (ScECO) and 2 routinely used clinical scales: the modified Wood Downes Ferres (WDFM), and the Hospital Sant Joan de Deu (HSJD). The relationship between the ScECO and the subsequent clinical progression (admission to the Paediatric Intensive Care Unit (PICU), days in hospital, and days of oxygen therapy) was also determined. Results: The study included a total of 59 patients, with a median age of 90 days (IQR: 30-270 days). The median ScECO score was 6 points (2-8) in the patients that did not require hospital admission, with 9 points (5-13.7) admitted to the ward, and 17 (14.5-18) in the patients who needed to be transferred from the ward to the PICU (P = .001). The ScECO had a moderate lineal association with the WDFM scale (rho = 0.504, P < .001) and the HSJD (rho = 0.518; P < .001). The ScECO was associated with admission to PICU [OR 2.5 (95% CI: 1.1-5.9); P = .035], longer hospital stay [1.2 days (95% CI: 0.55-1.86); P = .001] and duration of oxygen therapy [0.87 days (95% CI: 0.26-1.48); P = .006]. Conclusions: There is a moderate correlation between early lung ultrasound findings with the severity of the AB evaluated by the clinical scales, as well as some relationship with the clinical progression. Resumen: Objetivo: Evaluar la correlación entre hallazgos de la ecografía pulmonar realizada precozmente con las escalas de gravedad clínica y su asociación con la evolución posterior en la bronquiolitis aguda (BA) leve-moderada. Pacientes y métodos: Estudio observacional prospectivo. Se incluyó a lactantes con BA leve-moderada evaluados mediante ecografía pulmonar en las primeras 24 h tras la atención hospitalaria. Se graduó la afectación pulmonar (rango 0-50 puntos) sobre la base de un score ecográfico (ScECO). Se evaluó la correlación entre el ScECO y 2 escalas clínicas de uso habitual: escala de Wood Downes Ferres modificada (WDFM) y escala del Hospital Sant Joan de Déu (HSJD). Así mismo se valoró la asociación entre el ScECO y la evolución clínica posterior (ingreso en la Unidad de Cuidados Intensivos Pediátricos [UCIP], días de hospitalización y días de oxigenoterapia). Resultados: Se incluyó a 59 pacientes con una edad mediana de 90 días (RIQ: 30-270 días). La puntuación mediana del ScECO fue de 6 puntos (2-8) en los pacientes que no requirieron ingreso, 9 (5-13,7) en los ingresados en planta y 17 (14,5-18) en los pacientes que precisaron traslado de planta a la UCIP (p = 0,001). El ScECO tuvo una correlación lineal moderada con la escala de WDFM (rho = 0,504, p< 0,001) y HSJD (rho = 0,518; p < 0,001). El ScECO se asoció al ingreso en UCIP (OR 2,5 [IC del 95%: 1,1-5,9]; p = 0,035), mayor estancia hospitalaria (1,2 días [IC del 95%: 0,55, 1,86]; p = 0,001) y duración de oxigenoterapia (0,87 días [IC del 95%: 0,26, 1,48]; p = 0,006). Conclusiones: La ecografía pulmonar precoz se correlaciona de forma moderada con la gravedad de la BA evaluada por escalas clínicas y guarda cierta relación con la evolución clínica.